The relationship between physical fitness and shooting accuracy of professional basketball players - Haris Pojskić; Vlatko Šeparović; Melika Muratović; Edin Užičanin (Universidade Estadual Paulista (UNESP), 2014)
The aim of this study was to examine the relationships among physical fitness of professional Bosnian basketball players (n = 38) and shooting accuracy during one basketball season. A related, secondary aim was to examine relationships between basketball shooting assessments and competitive shooting accuracy during game play. Physical fitness components included: muscular endurance and aerobic endurance, lower and upper-body power, speed, agility, anaerobic capacity and anaerobic power. The specific basketball shooting accuracy was assessed by stationary and dynamic shooting assessments. Competitive shooting accuracy was represented by data collected during one basketball season for each player (free throw, field goal, and three-point %). Results of the regression analyses showed that there were significant positive relationships among shooting assessments and competitive shooting accuracy during game play. The relationship was stronger when the dynamic shooting tests were applied compared to the stationary tests. However, few or weak relationships existed among physical fitness components and competitive shooting accuracy. Only the power tests showed to be good predictors for shooting over longer distances. The findings support the inclusion of the dynamic basketball shooting accuracy tests in regular basketball assessment procedures as a valuable testing instrument.